Influence of Additives on Thermal Properties and Morphological of Magnetorheological Elastomer - Zarina Ku Ahmad, Ku; Khairi, MHA; Mazlan, SA (International Journal of Engineering and Technology, 2019)
Magnetorheological elastomers (MREs) are categorized as part of the smart materials class whose rheological properties can be altered under the influence of a magnetic field. MREs are fabricated by embedding soft magnetic particles such as carbonyl iron particles (CIPs) in a rubber matrix such as silicone and natural rubber. In this project, epoxidized natural rubber (ENR-50) is used as a base material with carbonyl iron particles. Sucrose Acetate Isobutyrate (SAIB) ester is added to the formulation to improve the viscosity and enhance the MRE properties. The isotropic MRE is fabricated using two roll mill and a compression mould. Various tests comprise mechanical, morphology, thermal and magnetic tests were conducted for MRE characterization purpose. The results showed that the addition of SAIB on the MRE had reduced 53% of viscosity in the rubber matrix compared to non-ester based MRE. Dispersion of magnetic particles is improved by the addition of ester as observed through Field Emission Scanning Electron Microscope (FESEM). Additionally, the thermal stability was also improved. Tensile strength of MRE consisting SAIB ester achieved maximum strength of 12.3 MPa and an elongation of 620% compared to non-ester based MRE.Â Â